Duo Lingo Application for Teaching Speaking Skills Class: Students' Perception of Speech Ability - Syafrizal Syafrizal; Niken Sekar Cahyaningrum; Tosi Rut Syamsun (Institut Agama Islam Negeri Palopo, 2022)
Effect of Duo Lingo application to improve speaking ability. Duo Lingo to enhance student speaking ability. There are several problems with speech fluency This study is intended to find out the effectiveness of the Duolingo application on students’ perception to improve their speaking skills. Thus, this study used a qualitative approach, especially using an ethnomethodology research design. Firstly, this study used a qualitative approach because the researcher is intended to reach the data from interviews students’ procedures for creating and managing a sense of objective reality. This study is involved 27 students of grade IX from one class. Almost all students know the application of Duolingo,The result of the questionnaire indicates that 10 Neutral, 15 Agree, 2 Strongly agree that Duolingo as media improves English skills. It indicates that most of the learners agree that Duolingo is a media to improve English skills. As a result, teachers should be encouraged to use this app in language instruction and learning. Furthermore, teachers must ensure that this application is capable of being used efficiently. Another significant factor to consider is the use of cell phones in the classroom because some schools restrict mobile phone use while the classroom.